Prevalence of Different Subtypes of Renal Cell Carcinoma among Patients who have Undergone Nephrectomy; Statistics of a Referral Medical Center in Iran - Mohajer, Zahra; Moradi, Afshin; Allameh, Farzad (Archives of Men’s Health, 2021)
Renal cell carcinoma (RCC) is the third most common genitourinary cancer in the world, and has the highest mortality rates among these types of cancers. In the present cross-sectional assessment, the prevalence of RCC subtypes in a sample of Iranian patients diagnosed with RCC which have undergone nephrectomy surgery between years 2014 to 2019 in a referral medical center has been investigated. We have studied 68 patients, including 47 male and 21 female individuals with an average age of 55. The patients have been studied for demographic and pathologic information such as age, sex, tumor size, tumor subtype, TNM staging, Fuhrman nuclear grading, and other pathological information. The statistical analysis was done via SPSS software version 21. Quantitative data were examined by T test and qualitative data were assessed by Chi square test. As we observed in the results, the most common RCC subtype among these patients was clear cell 53%, followed by papillary 22% and chromophobe 19%, emphasizing the higher rates of chromophobe RCC compared to the statistics worldwide.